(untitled) (European Journal of Pure and Applied Mathematics, 2026)
The mathematical model of bovine babesiosis with vaccination helps researchers understand disease spread, assess vaccine effectiveness, and make predictions to guide the development of vaccination strategies that protect cattle. This model uses a number known as the basic reproduction number R_0 to predict the spread of a disease in herds of cattle. The model predicts that the illness will eventually go spread if R_0<1 . It is predicted that the Babesiosis bovine disease will extinct persist if R_0>1.Knowing this makes it easier to create immunization plans that work. To combat babesiosis, a serious disease that is spread by ticks to cattle, a vaccination is desperately needed. Some further discussion on the optimal amount of bovine vaccination is discussed. Some numerical simulations are utilized to validate the theoretical results.